Ajustes da pressão arterial sistólica e diastólica de mulher hipertensa e diabética à diferentes intensidades do exercício resistido - Cruz, Angélica Cristiane da [UNESP]; Quitério, Robison José [UNESP]; Rodrigues, Pedro Henrique [UNESP]; Chagas, Eduardo Federighi Baisi; Silva, Cristiano Sales; Froio, Juliana Lôbo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: Lactate threshold below (Wasserman et al, 1973), in healthy individuals, physiological responses are stable, because the systems get to meet energy demand, so, there is a balance between consumption and supply of oxygen (Brooks, 1991), however, above the intensity LA observed slow increase in HR as a function of time due to the high concentration of lactate. These adjustments are well established during aerobic exercise, but lack evidence during resistance exercise. Objective: To investigate the settings of SBP and DBP below and above the lactate threshold during resistance exercise on a diabetic and hypertensive woman. Method: Was studied a woman of 55 years, hypertensive and diabetic. The heart rate was recorded during the protocol using a digital telemetry system previously validated (LOIMAALA et al, 1999; GAMELIN BERTHOIN, BOSQUET, 2006), consisting of a transmitter positioned at the height of the xiphoid process, and a monitor / receiver (polar RS800CX, polar Electro Oy, Kempele, Finland).The anaerobic threshold (AT) was determined during the performance of knee extension exercise in the Roman table. Voluntary performed 20 repetitions for one minute with 10% load obtained in the 1RM test and after stopping test blood was collected on the earlobe for lactate analysis. This same procedure was performed in series with subsequent increase of 10% in 10% of the maximum load to that observed up to the value correspondent fixed 4 mmol.L lactate, which was considered as the lactate threshold (DENADAI, 1995; HECK et al,1985).. The HR and R-Ri were recorded continuously for 65 seconds at rest, during isotonic contraction and 5 minutes of recovery. From these data were studied adjustments in systolic blood pressure and diastolic blood pressure at rest and during exercise. Results and Discussion: We used for this study intensities 10%, 20% and 40%, which data were obtained, respectively, resting SBP = 128, 121 and 133 rest DBP = 81, 76 and 92, HR rest = 70 14, 68.91, and 67.09. SBP year = 146, 161 and 234. DBP exercise = 95, 109 and 158 HR exercise = 80.64, 84.57 and 90.74. Variation in SBP = 18, 40 and 101. Variation DBP = 14, 33 and 66. Variation HR = 11.82, 17.79 and 26.36. The results of the study are in agreement with the literature when they show a considerable increase in HR, SBP and DBP. Conclusion: The increase in DBP and SBP are disproportionate load at intensities above the AT.

Introdução: Abaixo do limiar de lactato (WASSERMAN et al, 1973), em indivíduos saudáveis, as respostas fisiológicas são estáveis, em virtude de os sistemas conseguirem atender a demanda energética ou seja, existe um equilibrio entre o consumo e oferta de oxigênio (BROOKS, 1991), entretanto, em intensidade acima do LA, observa-se aumento lento da FC em função do tempo devido à alta concentração de lactato. Esses ajustes estão bem estabelecidos durante o exercício aeróbio, porém carecem de evidências durante exercício resistido. Objetivo: Investigar os ajustes da PAS e PAD abaixo e acima do limiar de lactato durante o exercício resistido em uma mulher diabética e hipertensa. Material e método: foi estudada uma mulher de 55 anos, hipertensa e diabética, com medicação otimizada. A Fc foi gravada durante o protocolo utilizando-se um sistema digital de telemetria validado previamente (LOIMAALA et al, 199; GAMELIN, BERTHOIN, BOSQUET, 2006), que consiste de um transmissor posicionado na altura do processo xifóide e um monitor/receptor (Polar RS800CX, Polar Electro Oy, Kempele, Finland). O limiar de anaerobiose (LA) foi determinado durante o exercício de extensão do joelho (mesa romana). A voluntária realizou 20 repetiçoes durante um minuto com 10% da carga obtida no teste de 1RM e após a interrupção do teste foi coletado sangue no lóbulo da orelha para análise do lactato. Esse mesmo procedimento foi realizado em séries subsequentes com acréscimo de 10% em 10% da carga máxima até que se observou o valor correspondente fixo de lactato de 4mmol.L o qual foi considerado como sendo o limiar de lactato (DENADAI, 1995, HECK et al, 1985). A Fc e os iRR foram registrados continuamente durante 65s de repouso, durante a contração isotônica e 5 minutos de recuperação. A partir desses dados foram estudados os ajustes da pressão arterial sistólica e pressão arterial diastólica em repouso e durante o esforço. Resultados e discussão: Foram utilizadas para esse estudo as intensidades de 10%, 20% e 40%, cujos dados obtidos foram, respectivamente: PAS repouso = 128, 121 e 133. PAD repouso = 81, 76 e 92, FC repouso = 70,14, 68,91 e 67,09. PAS exercício = 146, 161 e 234. PAD exercício = 95, 109 e 158. FC exercício = 80,64, 84,57 e 90,74. Variação da PAS = 18, 40 e 101. Variação da FC = 11,82, 17,79 e 26,36. Os resultados obtidos no estudo estão de acprdo com a literatura quando mostram um aumento considerável da FC, PAS e PAD. Conclusão: O aumento da PAD e PAS são desproporcionais a carga em intensidades acima do LA.
Keywords: Blood pressure; Lactate; Heart rate; Pressão arterial; Lactato; Frequência cardíaca